A SOLUTION IMPROVING SNR FOR MULTIRECEIVER SYNTHETIC APERTURE SONAR - Tĩnh (Journal of Military Science and Technology, 2021)
This paper proposes a solution to improve signal/noise ratio (SNR) for Synthetic aperture sonar (SAS) by reducing the receiver element size, increasing the number of pulses for coherent processing, and taking into account the variation of the propagation velocity vector during transmission as well as considering Doppler effect. With more complete consideration of physical processes rather than traditional solutions, the proposed solution can enhance SNR when the size of each receiver/transmitter element is decreased in order to improve the along-track resolution. The simulation results obtained from the solutions demonstrate the effectiveness of proposed solution.